Out-of Court Settlement of Disputes with an Entity Operating on the Financial Market as an Element of Consumer Protection - Bogusławski, Adrian (Journal of Finance and Financial Law, 2016)
The main issue analysed in this article is the topic of consumer protection and instruments that he may use, provided by the legislator. The author analysed, in particular, the issue of out-of-court settlement of a dispute with a financial institution, which was introduced on 1 January 2016. The author’s objective was to conduct a comparative analysis in the area of consumer protection – within the legal framework valid as of before the introduction of the Financial Ombudsman and after said institution was introduced. The author, focusing on out-of-court settlement of a dispute pointed out to advantages and drawbacks of such procedure – basing on the rules and regulations indicated in the so-called Complaint Act. Basing on the analysis carried out, the author presented certain conclusions concerning the assessment of the reasonability of introducing the institution of Financial Ombudsman and out-of-court settlement of disputes.